DIGITAL ORAL AUTOPSY (VIRTUAL AUTOPSY): AN UPDATE (Journal of Forensic Medicine & Toxicology, 2025)
The discipline of forensic dentistry is advancing and has a broader range. It has entrenched itself as a branch that is indispensable in dealing with medical and legal issues as well as identifying the deceased. Any identification of unidentified human remains must adhere to the highest forensic standards and must always entail the gathering of pin-point autopsy information. The procedure calls for a comparison of the acquired data with the premortem information of consistent reported missing persons and a final accord of the information. A mixture of graphical exterior body scanning and volumetric illustrations are used in the scalpel-free virtual autopsy, or “Virtopsy.” The gathering of dental information and observation of premortem and post-mortem panoramic radiography are two uses of virtual autopsy in forensic odontology. Without doing a regular dental autopsy, virtual autopsy enables forensic odontologists to examine jaws and teeth. The goal of “virtopsy” is to maximise traditional autopsy recording by using contemporary depictions. The advantages of virtopsy include its non-invasive method and examiner-independent, objective 3D documentation. This paper will examine recent developments in virtual autopsy.
Keywords: Oral Autopsy; Virtopsy; Forensic odontology